2019
DOI: 10.1038/s41467-019-10144-w
|View full text |Cite
|
Sign up to set email alerts
|

Activated Peyer′s patch B cells sample antigen directly from M cells in the subepithelial dome

Abstract: The germinal center (GC) reaction in Peyer′s patches (PP) requires continuous access to antigens, but how this is achieved is not known. Here we show that activated antigen-specific CCR6 + CCR1 + GL7 − B cells make close contact with M cells in the subepithelial dome (SED). Using in situ photoactivation analysis of antigen-specific SED B cells, we find migration of cells towards the GC. Following antigen injection into ligated intestinal loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 66 publications
4
54
0
4
Order By: Relevance
“…In the intestines, daughter cells derived from Lgr5+ intestinal stem cells at the intestinal crypt base differentiate into M cells upon receiving stimulation via the cytokine receptor activator of nuclear factor-kB ligand (RANKL) (de Lau et al, 2012) and expression of the transcription factors Spi-B (Kanaya et al, 2012) and Sox8 (Kimura et al, 2019a). M cells transport antigens from the mucosal surface into lymphoid tissues to immune cells that inhabit a unique pocket structure at their basal side (Kolesnikov et al, 2020;Komban et al, 2019). Mice lacking intestinal M cells have delayed development of mucosal antibody (IgA)-secreting plasma cell responses due to impaired Peyer's patch germinal center (GC) formation and T follicular helper (Tfh) cell differentiation and develop more severe pathology when infected with intestinal pathogens such as Citrobacter rodentium (Nakamura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the intestines, daughter cells derived from Lgr5+ intestinal stem cells at the intestinal crypt base differentiate into M cells upon receiving stimulation via the cytokine receptor activator of nuclear factor-kB ligand (RANKL) (de Lau et al, 2012) and expression of the transcription factors Spi-B (Kanaya et al, 2012) and Sox8 (Kimura et al, 2019a). M cells transport antigens from the mucosal surface into lymphoid tissues to immune cells that inhabit a unique pocket structure at their basal side (Kolesnikov et al, 2020;Komban et al, 2019). Mice lacking intestinal M cells have delayed development of mucosal antibody (IgA)-secreting plasma cell responses due to impaired Peyer's patch germinal center (GC) formation and T follicular helper (Tfh) cell differentiation and develop more severe pathology when infected with intestinal pathogens such as Citrobacter rodentium (Nakamura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the early IgA response occurs without clonal selection in CCR6 + B cells of the SED. This is in contrast to other LNs, in which B cell clones that exhibit low affinity to Ags fail to survive, and high-affinity Ag receptor-expressing B cell clones are preferentially selected for differentiation into early plasmablasts in GCs ( 81 , 82 ). CCR6 + B cells localized to the SED generally encounter Ags that have been transcytosed by M cells.…”
Section: Induction and Regulation Of Mucosal Abs In The Gastrointestimentioning
confidence: 62%
“…Increased antigen trafficking into the Peyer’s patch would stimulate naïve lymphocytes. This could be enhanced by activated antigen-specific B cells that can sample antigens directly from M cells and migrate to the GC (Komban et al, 2019). Additional mechanisms beyond antigen transcytosis could also contribute to increased IgA production and GC reactions in aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the intestines, daughter cells derived from Lgr5+ intestinal stem cells at the intestinal crypt base differentiate into M cells upon RANKL stimulation (de Lau et al, 2012) and expression of the transcription factors Spi-B (Kanaya et al, 2012) and Sox8 (Kimura et al, 2019a). M cells transport antigens from the mucosal surface into lymphoid tissues to immune cells that inhabit a unique pocket structure at their basal side (Kolesnikov et al, 2020; Komban et al, 2019). Mice lacking intestinal M cells have delayed development of IgA-secreting plasma cell responses due to impaired germinal centre (GC) formation and T follicular helper (Tfh) cell differentiation (Rios et al, 2016).…”
Section: Introductionmentioning
confidence: 99%